Pengaruh Volatilitas Penjualan, Volatilitas Arus Kas Operasi Dan Tingkat Hutang Terhadap Persistensi Laba: Studi Empiris Pada Perusahaan Sektor Consumer Cyclicals Yang Terdaftar Di Bursa Efek Indonesia (Bei) Periode 2020 – 2022 - Puspita, Opi; Poerwati, Tjahjaning (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to test and find empirical evidence that strengthens the research model as well as analyzing and serving as teaching material regarding the influence of sales volatility, operating cash flow volatility and debt levels on profit persistence (empirical study on consumer cyclicals sector companies listed on the IDX for the 2020-2020 period). 2022). The method used in sampling is Purposive Sampling. The data used is secondary data in the form of financial reports of companies listed on the IDX from 2020 to 2022. The number of samples used in this research was 105 data. The results obtained in this research show that the Sales Volatility variable has an effect on Profit Persistence, Operating Cash Flow Volatility has an effect on Profit Persistence, Debt Level has an effect on Profit Persistence in Consumer Cyclicals Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2020 - 2022 Period.